A CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND BATAK TOBA LANGUAGE IN VERBAL AFFIXES - Purba, Desica Florensia; Malau, Fenni; Siahaan, Mikhael L. A; Napitupulu, Selviana (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
Indonesia is one of the largest countries in the world which consists of various islands and tribes.  One of the tribes is the Batak Toba.  Batak Toba is a native tribe originating from North Sumatra because most of the Batak Toba people live in North Sumatra.  In this journal the author discusses a comparative between verbal affixes in English and Batak Toba Language. Which is English such as the source and Batak Toba Language as the target language.  This article aims to determine the difference between verbal affixes in English and Batak Toba Language.  The implement used is documentation and reading several other articles correlated to verbal affixes in English and Toba Batak Toba Language.  Data were analyzed using descriptive analysis comparative studies. The research technique used is descriptive analysis to discovery the differences Verbal Affixes between English and Batak Toba Language. The findings reveal that the comparison of verbal affixes in English and Batak Toba Language in the recount text provided shows that the types of verbal affixes in English and Batak Toba Language are different. Verbal affixes in English and Batak Toba Language have differences, namely in English there are 3 types of affixes, namely, prefixes, suffixes, and infixes and these three types have more types in them. While in Toba Batak language there are 4 types of affixes, namely prefixes, suffixes, infixes, and confixes.